2017
DOI: 10.1007/s40618-017-0778-8
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid dysfunctions secondary to cancer immunotherapy

Abstract: Background Immunotherapy is a firmly established pillar in the treatment of cancer, alongside the traditional approaches of surgery, radiotherapy, and chemotherapy. Like every treatment, also cancer immunotherapy causes a diverse spectrum of side effects, collectively referred to as immune-related adverse events. Objective This review will examine the main forms of immunotherapy, the proposed mechanism(s) of action, and the incidence of thyroid dysfunctions. Methods A comprehensive MEDLINE search was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(43 citation statements)
references
References 101 publications
1
41
1
Order By: Relevance
“…Hyperthyroidism irAEs are often detected before hypothyroidism, but at lower rates than hypothyroidism in patients treated with cancer immunotherapy, including atezolizumab. 41 We found that carrying a single risk allele was sufficient to increase individual risk of hyperthyroidism ( figure 5A ; univariable p=0.0072; HR=1.89; 95% CI 1.19 to 3.02). In contrast, patients homozygous for the risk allele of rs2476601 were more likely to develop atezolizumab-induced hypothyroidism than heterozygous carriers and non-carriers ( figure 5B ; univariable p=0.0029; HR=4.89; 95% CI 1.72 to 13.91).…”
Section: Resultsmentioning
confidence: 76%
“…Hyperthyroidism irAEs are often detected before hypothyroidism, but at lower rates than hypothyroidism in patients treated with cancer immunotherapy, including atezolizumab. 41 We found that carrying a single risk allele was sufficient to increase individual risk of hyperthyroidism ( figure 5A ; univariable p=0.0072; HR=1.89; 95% CI 1.19 to 3.02). In contrast, patients homozygous for the risk allele of rs2476601 were more likely to develop atezolizumab-induced hypothyroidism than heterozygous carriers and non-carriers ( figure 5B ; univariable p=0.0029; HR=4.89; 95% CI 1.72 to 13.91).…”
Section: Resultsmentioning
confidence: 76%
“…This mechanism of action is different from other drug‐induced AIHA where a drug (often a cephalosporin) is absorbed to the red blood cell membrane which then triggers the development of autoantibodies to the red cell membrane, or when a drug neoantigen cross reacts with a red cell antigen (for example methyl dopa) . It is speculated that CPIs cause a random activation of the immune system resulting in the formation of autoantibodies, activation of T‐cell clones, and diminishing the function of regulatory T cells . AIHA is not the only yet rare hematologic complication of CPIs.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 It is speculated that CPIs cause a random activation of the immune system resulting in the formation of autoantibodies, activation of T-cell clones, and diminishing the function of regulatory T cells. 33 AIHA is not the only yet rare hematologic complication of CPIs. Several cases of autoimmune neutropenia, thrombocytopenia, and even pancytopenia were recently published.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high mutation burden associated with increased immunogenicity, immunotherapy with immune checkpoint inhibitors has been utilized for advanced and metastatic HTCs. The monoclonal antibodies against programmed cell death protein 1 (PD-1), PD ligand 1 (PD-L1), and cytotoxic T lymphocyte associated antigen 4 (CTLA-4), have been utilized either as monotherapies or combination therapies [81]. Clinical trials which are focused on combination therapies for HTC include targeting the immunological landscape of HTC along with tumor angiogenesis, tyrosine kinase receptors, and overactive mTOR signaling.…”
Section: Targeted Therapies For Htcmentioning
confidence: 99%